The Construct Of New Media Communication Domain As Television Broadcast Mediamorphosis Output (Television Morphosis) - Prabu REVOLUSI (Indonesia Strategic Sustainability, 2022)
The adaptation process must be carried out to enable television to become a new media entity and avoid competing with media entities born in the new media ecosystem (organic new media entities). This research provides a road map of television change (televisimorphosis), which originally appeared in Fidler broadcasting communication to television within the domain of new media communication. The adaptation process follows the stages of coevolution, convergence, and complexity. One of the previous findings is that coevolution is the stage television should avoid in media adaptation. This finding confirms the data regarding why television is struggling to adapt to the new media ecosystem. Fidler's mediamorphosis is used as the rationale for this research. However, Fidler’s work does not sufficiently explain new media, so we re-constructed the communication domain concept built by Fidler by building a new communication domain, namely the new media communication domain. The results of this study propose the construction of a new media communication domain. The communication domain will be divided into four domains, including the domain we added, called the New Media Communications Domain, or IoT (Internet of Things) Communications Domain. Within the multidomain convergence process, terms of the format will cross over and give rise to a new character for television, namely Panoramic (Audio Visual Text).